Disrupted myelin lipid metabolism differentiates frontotemporal dementia caused by GRN and C9orf72 gene mutations - Oana C. Marian; Jonathan D. Teo; Jun Yup Lee; Huitong Song; John B. Kwok; Ramon Landin-Romero; Glenda Halliday; Anthony S. Don (Acta Neuropathologica Communications, 2023)
Abstract Heterozygous mutations in the GRN gene and hexanucleotide repeat expansions in C9orf72 are the two most common genetic causes of Frontotemporal Dementia (FTD) with TDP-43 protein inclusions. The triggers for neurodegeneration in FTD with GRN (FTD-GRN) or C9orf72 (FTD-C9orf72) gene abnormalities are unknown, although evidence from mouse and cell culture models suggests that GRN mutations disrupt lysosomal lipid catabolism. To determine how brain lipid metabolism is affected in familial FTD with TDP-43 inclusions, and how this is related to myelin and lysosomal markers, we undertook comprehensive lipidomic analysis, enzyme activity assays, and western blotting on grey and white matter samples from the heavily-affected frontal lobe and less-affected parietal lobe of FTD-GRN cases, FTD-C9orf72 cases, and age-matched neurologically-normal controls. Substantial loss of myelin-enriched sphingolipids (sulfatide, galactosylceramide, sphingomyelin) and myelin proteins was observed in frontal white matter of FTD-GRN cases. A less-pronounced, yet statistically significant, loss of sphingolipids was also observed in FTD-C9orf72. FTD-GRN was distinguished from FTD-C9orf72 and control cases by increased acylcarnitines in frontal grey matter and marked accumulation of cholesterol esters in both frontal and parietal white matter, indicative of myelin break-down. Both FTD-GRN and FTD-C9orf72 cases showed significantly increased lysosomal and phagocytic protein markers, however galactocerebrosidase activity, required for lysosomal catabolism of galactosylceramide and sulfatide, was selectively increased in FTD-GRN. We conclude that both C9orf72 and GRN mutations are associated with disrupted lysosomal homeostasis and white matter lipid loss, but GRN mutations cause a more pronounced disruption to myelin lipid metabolism. Our findings support the hypothesis that hyperactive myelin lipid catabolism is a driver of gliosis and neurodegeneration in FTD-GRN. Since FTD-GRN is associated with white matter hyperintensities by MRI, our data provides important biochemical evidence supporting the use of MRI measures of white matter integrity in the diagnosis and management of FTD.